The Role of Leadership in Organizational Productivity and Efficiency - Ferreira, Felipe; Medeiros, Luis (Revista Interface Tecnológica, 2025)
The article analyzes how different leadership styles influence productivity and efficiency within organizations. The main objective of the study is to understand the impact of leadership on team performance, considering aspects such as motivation, communication, and organizational climate. To achieve this, a bibliographic research methodology was employed, based on contemporary authors in the field of management and organizational behavior. The results indicate that transformational and situational leadership styles are the most effective in promoting engagement, cohesion, and employee motivation. It is observed that leaders who practice active listening, demonstrate empathy, and possess emotional intelligence strengthen the work environment and increase team productivity. The research also highlights the importance of strategic leadership in aligning organizational objectives with the individual purposes of employees. It is concluded that effective leadership acts as an agent of transformation, contributing to the achievement of sustainable results and the construction of a solid organizational culture that is adaptable to contemporary challenges